Cognitive decline and brain pathology in aging – need for a dimensional, lifespan and systems vulnerability view. Issue 3 (15th April 2014) - Walhovd, Kristine B; Fjell, Anders M; Espeseth, Thomas
<x xml:space="preserve">Abstract</x> Changes in brain structure and activity as well as cognitive function are commonly seen in aging. However, it is not known when aging of brain and cognition starts, and how much of the changes observed in seemingly healthy older adults that can be ascribed to incipient neurodegenerative disease. Recent research has yielded evidence that the borders between development and aging sometimes can be fuzzy, as can the borders between dementing disease and normal age changes. In this review, we argue that many factors affecting cognitive decline and dementia represents quantitative rather than qualitative differences in characteristics that commonly exist in the population. Further, factors known to affect brain and cognition in aging will often do so through a life‐long accumulation of impact, and does not need to be specific to aging. And finally, a host of environmental and genetic factors and their interplay determine optimal aging, leaving room for potential for environmental interventions to affect the outcome of the aging process. Together, we argue that these factors call for a dimensional rather than categorical, lifespan rather than aging, and multidimensional systems‐vulnerability rather than simple "hypothetical biomarker" model of age‐associated cognitive decline and dementia. This has implications for how we should view lifespan trajectories of change in brain and cognitive function, and how we can study, prevent, diagnose and treat age‐associated cognitive deficits.